Peran Instagram dalam Kampanye Presiden Indonesia Tahun 2024 - Afri Syaharani; Moh. Gufron; Sanjiana Silla Nurhikmah; Tegar Pijar Matahari; Pia Khoirotun Nisa (CV. ITTC INDONESIA, 2024)
This research aims to find out the role of the Instagram platform as a digital platform that makes the 2024 presidential election campaign a success, as well as finding out what the advantages of Instagram social media are so that it can influence public opinion in the 2024 presidential election campaign. This research uses qualitative instruments with data collection methods through literature review. In searching for theoretical foundations and theoretical studies, the speaker actively looks for theoretical material from various books according to the chosen theme. Meanwhile, in the case study study, the speaker looks at the case perspective from the reality of the 2024 presidential campaign. In this discussion, it is concluded that the role of Instagram in the 2024 Indonesian Presidential Election Campaign, namely that Instagram is a platform that plays a role in facilitating the dissemination of information in the presidential candidate campaign. 2024, because Instagram is a platform that has many active users, and when using it, the Instagram features are free to be accessed by anyone for free so that this platform becomes a campaign field in the online network which is very influential because the majority of internet users definitely have Instagram. Then it is added with an algorithm that can be adjusted according to user interests so that presidential candidates can manage campaign content in more detail according to existing algorithm data. Instagram also has quite a big influence in guiding public opinion for several reasons, namely, Firstly, the High Penetration of Instagram Users among Millennials. Second, an attractive visual communication style. Third, real-time and viral interactions.